1961
DOI: 10.1111/j.1365-2672.1961.tb00253.x
|View full text |Cite
|
Sign up to set email alerts
|

CHARACTERISTICS OF ENGLISH ISOLATES OF ERWINIA AMYLOVORA (BURRILL) WINSLOW ET AL.

Abstract: SUMMARY The characteristics of 38 English isolates of Erwinia amylovora were studied independently at East Malling Research Station and at the National Agricultural Advisory Service Laboratories at Wye. The results from both laboratories were similar and indicate considerable physiological homogeneity amongst the isolates. The joint findings are described and compared with those of other authors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0
1

Year Published

1987
1987
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(35 citation statements)
references
References 29 publications
1
33
0
1
Order By: Relevance
“…The pathogenicity was evaluated by symptoms of fire blight on inoculation leaves of apple seedling, 114 strains gave positive results with all E. amylovora strains assayed, except 16 strains which did not produce symptoms after two weeks on pear fruits as reported by other authors [18]- [19]. These leaves showed necrosis that started in the leaf wounds and progressed via the veins into the petioles, and droplets of ooze developed on the leaves.…”
Section: B Pathogenicity Testsmentioning
confidence: 93%
“…The pathogenicity was evaluated by symptoms of fire blight on inoculation leaves of apple seedling, 114 strains gave positive results with all E. amylovora strains assayed, except 16 strains which did not produce symptoms after two weeks on pear fruits as reported by other authors [18]- [19]. These leaves showed necrosis that started in the leaf wounds and progressed via the veins into the petioles, and droplets of ooze developed on the leaves.…”
Section: B Pathogenicity Testsmentioning
confidence: 93%
“…Using two tubes per strain in two independent experiments, one strain was negative and three strains hydrolysed gelatin slower than the rest of the tested strains. Variability in gelatin hydrolysis for E. amylovora was already reported (Billing et al 1961;Donat et al 2005). Moreover, in API 20E test Donat et al (2005) found only four strains positive for gelatin hydrolysis out of 61 E. amylovora strains tested.…”
Section: Discussionmentioning
confidence: 87%
“…Moreover, in API 20E test Donat et al (2005) found only four strains positive for gelatin hydrolysis out of 61 E. amylovora strains tested. It has also been noticed in some E. amylovora strains that weak gelatin hydrolysis correspond to weak production of ooze in inoculated pear fruits (Billing et al 1961). However, we could not confirm this since our strains produced typical lesions on immature pear fruits with oozing at the inoculation site 2 days after inoculation.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In the present study, E. amylovora cells kept at 5ºC in sterile irrigation water retained their culturability on King's B solid medium at similar levels to those of the inoculation time while a decline was observed in the microcosms incubated at 26ºC within three months. Then, low temperature does not seem to affect negatively its survival in water and it has been described that this pathogen can grow at 3-5ºC [Billing et al, 1961]. The former suggest that the overwintering of E. amylovora may be more related to the lack of nutrients in the plant during host dormancy [Vanneste and Eden-Green, 2000] than to low temperatures.…”
Section: A42 Pathogenicity Assaysmentioning
confidence: 92%